Intercultural learning experiences and English communication self-efficacy among aviation vocational students - Fatmawati Fatmawati; Laila Rochmawati; Meita Maharani Sukma; Edmond Brianaldy Tahu Klau; Lusiana Dwi Kusumayati; Lady Silk Moonlight (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2026)
Globalization increasingly demands graduates who are able to communicate across cultures confidently and appropriately. However, limited evidence explains how culturally diverse students in semi-military vocational settings experience intercultural learning, particularly when language barriers and differing expectations shape their academic and social adjustment. This study explores the motivations, perceived benefits, challenges, and intercultural learning experiences of foreign students enrolled at Surabaya Aviation Polytechnic. Using a qualitative case study approach, data were collected from 18 Timor-Leste students through semi-structured interviews and open-ended questionnaires, and analyzed using deductive–inductive thematic analysis with data triangulation. The conceptual frameworks of intercultural communicative competence (ICC), cultural intelligence (CQ), and self-efficacy in English use informed the construction of interview guides and the interpretation of findings. Results reveal six key motivations for studying abroad, mainly career advancement, institutional reputation, and program practicality. Nevertheless, students experienced a clear gap between expectations and reality. Limited interaction with local peers, regional language accents, and low confidence in using English led to reduced frequency of intercultural encounters, social withdrawal, and stagnation in ICC development. Personal factors such as introversion and language anxiety further constrained participation. The findings suggest that authentic intercultural exposure, confidence-building strategies, and structured cultural preparation are essential to support students’ integration and learning. Practically, institutions should provide mentoring, communication simulations, and media-based cultural orientation to improve students’ readiness, emotional regulation, and self-efficacy. The study contributes to the literature by highlighting how intercultural learning unfolds in a unique vocational aviation context and by proposing practical approaches to enhance students’ intercultural development.